2013
DOI: 10.1007/s15010-012-0387-6
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin reduces the risk of hemolytic uremic syndrome in patients with Escherichia coli O104:H4-associated diarrhea

Abstract: In our E. coli O104:H4-infected patients, treatment of diarrhea with antibiotics did not increase the risk of HUS. Significantly fewer patients treated with ciprofloxacin developed HUS than patients who did not receive ciprofloxacin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 15 publications
0
21
0
3
Order By: Relevance
“…[15][16][17] However, recent reports during a German outbreak established new evidence regarding antibiotic usage. [18][19][20] In conclusion, Acinetobacter infection should be considered as a plausible cause of typical HUS in cases with no E. coli infection. The high frequency and degree of adaptability and transformability among some strains of Acinetobacter spp.…”
Section: Discussionmentioning
confidence: 91%
“…[15][16][17] However, recent reports during a German outbreak established new evidence regarding antibiotic usage. [18][19][20] In conclusion, Acinetobacter infection should be considered as a plausible cause of typical HUS in cases with no E. coli infection. The high frequency and degree of adaptability and transformability among some strains of Acinetobacter spp.…”
Section: Discussionmentioning
confidence: 91%
“…Exposure to antibiotics also increases the risk of HUS in children (114). However, recent data demonstrated that treatment with ciprofloxacin reduced the risk of HUS in patients infected with the 2011 German O104 STEC strain (116). These data are supported by a recent meta-analysis of studies between 1980 and 2011 (117).…”
Section: Escherichia Colimentioning
confidence: 90%
“…Therefore, bacteremia during EHEC infection represents a new therapeutic challenge. However, a 2011 outbreak in Germany linked to EHEC O104:H4 ( 13 ) underscored the potential benefit of certain antibiotics when HUS occurs ( 14 , 15 ). Thus, the use of antibiotics during EHEC infections remains a source of debate ( 2 , 16 ).…”
mentioning
confidence: 99%